Non-conventional cement-based composites reinforced with vegetable fibers: a review of strategies to improve durability - Santos, Sérgio Francisco dos [UNESP]; Tonoli, Gustavo Henrique Denzin; Mejia, J. E. B.; Fiorelli, J.; Savastano Júnior, Holmer (Inst Ciencias Construccion Eduardo Torroja, 2015)
The present review shows the state-of-art on the approachs about improving the processing, physical-mechanical performance and durability of non-conventional fiber-cement composites. The objective of this review is to show some of these strategies to mitigate the degradation of the vegetable fibers used as reinforcement in cost-effective and non-conventional fiber-cement and, consequently, to improve their mechanical and durability properties for applications in the housing construction. Beyond the introduction about vegetable fibers, the content of this review is divided in the following sections: (i) surface modification of the fibers; (ii) improving fiber-to-cement interface; (iii) natural pozzolans; (iv) accelerated carbonation; (v) applications of nanoscience; and (vi) principles of functionally graded materials and extrusion process were briefly discussed with focus on future research needs.
Keywords: Fiber treatment; Accelerated carbonation; Nanotechnology; Functionally graded materials; Extrusion process